Daily rhythm of insecticide susceptibility in the silkworm Bombyx mori. Issue 2 (3rd March 2016) - Egi, Yuichi; Sakamoto, Katsuhiko
Abstract : This study investigated daily changes in susceptibility to insecticides in the silkworm Bombyx mori (Lepidoptera: Bombycidae). The daily rhythm of permethrin susceptibility in fifth instar larvae of the p63-silkworm strain was significant, with the lowest mortality rate during the late photophase under a 12-h light–12-h dark cycle. The rhythms were similar whether permethrin was intraperitoneally injected into hemolymph or topically applied to the dorsal abdomen. Drug intake through the cuticle probably did not significantly contribute to the organization of this susceptibility rhythm. We also found that the daily susceptibility profiles depended on insecticide type and silkworm strain. Temporal susceptibility variations might be attributable to the drug metabolic system. To our knowledge, this is the first description of an insecticide susceptibility rhythm in the larval stage of lepidopteran insects. Specifically timed delivery of insecticides might enable more efficient control of pest caterpillars that cause serious crop damage.